Depressive symptoms and adherence to cardiometabolic therapies across phases of treatment among adults with diabetes: the Diabetes Study of Northern California (DISTANCE) - Bauer AM; Parker MM; Moffet HH; Schillinger D; Adler NE; Adams AS; Schmittdiel JA; Katon WJ; Karter AJ (Patient Preference and Adherence, 2017)
Amy M Bauer,1 Melissa M Parker,2 Howard H Moffet,2 Dean Schillinger,3,4 Nancy E Adler,5 Alyce S Adams,2 Julie A Schmittdiel,2 Wayne J Katon,1,† Andrew J Karter2 1Department of Psychiatry and Behavioral Sciences, University of Washington School of Medicine, Seattle, WA, 2Kaiser Permanente Northern California, Oakland, 3Division of General Internal Medicine, University of California, San Francisco, 4Center for Vulnerable Populations, San Francisco General Hospital and Trauma Center, 5Department of Psychiatry and Pediatrics, Center for Health and Community, University of California, San Francisco, CA, USA †Dr Wayne J Katon passed away on March 1, 2015 Objective: Among adults with diabetes, depression is associated with poorer adherence to cardiometabolic medications in ongoing users; however, it is unknown whether this extends to early adherence among patients newly prescribed these medications. This study examined whether depressive symptoms among adults with diabetes newly prescribed cardiometabolic medications are associated with early and long-term nonadherence. Patients and methods: An observational follow-up of 4,018 adults with type 2 diabetes who completed a survey in 2006 and were newly prescribed oral antihyperglycemic, antihypertensive, or lipid-lowering agents within the following year at Kaiser Permanente Northern California was conducted. Depressive symptoms were examined based on Patient Health Questionnaire-8 scores. Pharmacy utilization data were used to identify nonadherence by using validated methods: early nonadherence (medication never dispensed or dispensed once and never refilled) and long-term nonadherence (new prescription medication gap [NPMG]: percentage of time without medication supply). These analyses were conducted in 2016. Results: Patients with moderate-to-severe depressive symptoms had poorer adherence than nondepressed patients (8.3% more patients with early nonadherence, P=0.01; 4.9% patients with longer NPMG, P=0.002; 7.8% more patients with overall nonadherence [medication gap >20%], P=0.03). After adjustment for confounders, the models remained statistically significant for new NPMG (3.7% difference, P=0.02). There was a graded association between greater depression severity and nonadherence for all the models (test of trend, P<0.05). Conclusion: Depressive symptoms were associated with modest differences in early and long-term adherence to newly prescribed cardiometabolic medications in diabetes patients. Interventions targeting adherence among adults with diabetes and depression need to address both initiation and maintenance of medication use. Keywords: medication adherence, depression, diabetes mellitus, type 2 diabetes, Patient Health Questionnaire-8, PHQ-8, antihypertensive, hypoglycemic, hypolipidemic agents, pharmacoepidemiology, observational cohort study